LEARNING ALGEBRA IN 7-9TH FORMS WITH USING OF PROGRAM METHOD “LIBRARY OF ELECTRONIC OBVIOUSNESS” (Journal of Information Technologies in Education (ITE), 2011)
In this article the information about assignment of the pedagogical program method “Library of electronic obviousness “Algebra for 7-9th forms” and its main characteristics are given. Also methodic aspects of carrying the algebra lessons are shown.
Keywords: algebra lesson; pedagogical program method; supporting notes